Multiple emulsions : (Wiley-Interscience, 2008)
In theory, multiple emulsions have significant potential for breakthrough applications in food, agricultural, pharmaceutical, nutraceutical, and cosmetic industries in which they can facilitate the sustained release and transport of active material. However, in practice, multiple emulsions are thermodynamically unstable. This book presents recent findings that can help formulators understand how to enhance their stability. With chapters contributed by leading experts from around the world, it covers the definition and properties of multiple emulsions, their formation and stability, and potential applications, with an emphasis on medical and pharmaceutical applications. In one definitive resource, it presents recent findings and achievements in the field, including: New theoretical approaches and modeling to characterize the transport mechanism; Droplet size reduction and increased shelf life stability through the use of polymeric amphiphiles and complex adducts; The use of new emulsification techniques to enhance the monodispersibility of the droplets; Potential applications in drug delivery systems where clinical studies have proven their efficacy.